Overproduction of dihydrofolate reductase and gene amplification in methotrexate-resistant Chinese hamster ovary cells. - Flintoff, W F (1982)
Stable isolates of Chinese hamster ovary cells that are highly resistant to methotrexate have been selected in a multistep selection process. Quantitative immunoprecipitations have indicated that these isolates synthesize dihydrofolate reductase at an elevated rate over its synthesis in sensitive cells. Restriction enzyme and Southern blot analyses with a murine reductase cDNA probe indicate that the highly resistant isolates contain amplifications of the dihydrofolate reductase gene number. Depending upon the parenteral line used to select these resistant cells, they overproduce either a wild-type enzyme or a structurally altered enzyme. Karyotype analysis shows that some of these isolates contain chromosomes with homogeneously staining regions whereas others do not contain such chromosomes.